Letter from Robert S. Mulliken to Harrison Shull, 1961 - Mulliken, Robert Sanderson (1961)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, concerning the development of several scientific, analytical instruments, as well as a proposal to establish a program in Chemical Physics.
Keywords: Shull, Harrison; Nuclear magnetic resonance spectroscopy; Scientific apparatus and instruments; Mulliken, Robert Sanderson; Chemists; Quantum chemistry; Varian Associates; Nobel Prize winners; Physicists